PERANAN ANGGRAN BIAYA PRODUKSI DALAM MENINGKATKAN EFEKTIVITAS DAN EFESIENSI PENGENDALIAN BIAYA PRODUKSI PADA PT. TOLAN TIGA INDONESIA - Natasya Bella Safira Marpaung; Sri Elviani; Zulkifli Siregar; Abdul Rasyid (JRAM (Jurnal Riset Akuntansi Multiparadigma), 2021)
This research was conducted to see the role of the production cost budget in increasing the effectiveness and efficiency of controlling production costs at PT. Tolan Tiga Indonesia in North Sumatra. The type of data used is quantitative data. Sources of data used are primary and secondary data. Data collection methods used for this research are documentation, observation and interviews. The data analysis technique used is descriptive analysis.  The results showed that the company was still less effective and efficient in carrying out production budget activities, because PT. Tolan Tiga Indonesia has not attempted to improve production cost control in order to increase its effectiveness and efficiency because there are still many levels of unfortunate or unforable variance between the relationship and the company budget. It can be seen in 2016 and 2017 the realization and production costs of PT. Tolan Tiga Indonesia in North Sumatra experienced a favorable variance where the realization rate decreased compared to the company budget. The unfavorable deviation was caused by high staff allowance expenses, increased overhead expenses, increased management expenses, increased depreciation expenses and increased third party depreciation expenses.